The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1371/journal.pone.0118368
|View full text |Cite
|
Sign up to set email alerts
|

A New Approach to Improving Healthcare Personnel Influenza Immunization Programs: A Randomized Controlled Trial

Abstract: BackgroundHealthcare personnel influenza immunization rates remain sub-optimal. Following multiple studies and expert consultations, the “Successful Influenza Immunization Programs for Healthcare Personnel: A Guide for Program Planners” was produced. This trial assessed the impact of the Guide with facilitation in improving healthcare personnel influenza immunization rates in Canadian healthcare organizations.MethodsA sample of 26 healthcare organizations across six Canadian provinces (ON, MB, NS, BC, SK, NL) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(35 citation statements)
references
References 21 publications
0
35
0
Order By: Relevance
“…Tables S1 and S2 report the synthesis of the included studies. Seven were randomized controlled trials [50][51][52][53][54][55][56], six were pre-post surveys [57][58][59][60][61][62], one assessed the vaccination rate trend in accordance with the types of interventions [63], 11 were cross sectional studies [64][65][66][67][68][69][70][71][72][73][74], and two were interrupted time series studies [75,76]. The majority (52%) of the selected studies were performed in the USA, which was followed by Europe (33%), Canada (11%), and Australia (4%).…”
Section: Discussing Vaccination Policy During New Hire Orientation 3omentioning
confidence: 99%
See 2 more Smart Citations
“…Tables S1 and S2 report the synthesis of the included studies. Seven were randomized controlled trials [50][51][52][53][54][55][56], six were pre-post surveys [57][58][59][60][61][62], one assessed the vaccination rate trend in accordance with the types of interventions [63], 11 were cross sectional studies [64][65][66][67][68][69][70][71][72][73][74], and two were interrupted time series studies [75,76]. The majority (52%) of the selected studies were performed in the USA, which was followed by Europe (33%), Canada (11%), and Australia (4%).…”
Section: Discussing Vaccination Policy During New Hire Orientation 3omentioning
confidence: 99%
“…With the EPHPP quality assessment tool [49], seven out of the 27 studies included in the current review were assessed as works of 'strong' quality [50][51][52][53][54][55][56], five papers of 'moderate' quality [58,63,72,74,75], and the remaining 15 works as 'weak' quality [56,[59][60][61][62][64][65][66][67][68][69][70][71]73,76]. Results of the application of the EPHPP quality assessment tool are reported in Tables S1 and S2.…”
Section: Discussing Vaccination Policy During New Hire Orientation 3omentioning
confidence: 99%
See 1 more Smart Citation
“…The use of vaccines has been promoted to protect people of all ages against several diseases by emphasising the importance of vaccinations in adults, no longer making vaccinations a proprietary right reserved for children (World Health Organization (WHO) ). In medical fields, the most crucial issue is maintaining the immunity of healthcare personnel (HCP) to effectively reduce the risk of pathogen transmission by HCP to patients (Centers for Disease Control & Prevention, ; Chambers et al, ). Moreover, vaccinating HCP reduces personnel and labour costs during an epidemic (Ozisik, Tanriover, Altınel, & Unal, )…”
Section: Introductionmentioning
confidence: 99%
“…In particular, HCP who worked in obstetrics and gynaecology, paediatrics, and emergency departments, infectious disease division, and postpartum nursing care centres had first priority (Taiwan Centers for Disease Control, ). Most existing studies on HCP immunisations mainly focused on influenza and Hep B vaccines and reported that HCP exhibited different behavioural patterns towards different vaccine types (Adekanle, Ndububa, Olowookere, Ijarotimi, & Ijadunola, ; Chambers et al, ; Karaivazoglou et al, ). However, HCPs’ behavioural patterns towards MMR, varicella and DTaP vaccines are unclear.…”
Section: Introductionmentioning
confidence: 99%